Arduino Based Smart Solar Mower - Virendra Swaroop Sangtani; Krati Lakhani; Kartik Soni; Kanishk Pratap Singh Rathore; Dushyant Kalodia; Karan Vashishth (International Journal of Engineering and Management Research, 2024)
This study recommends an Arduino-based smart solar grass cutter to increase user productivity and accessibility. This paper presents the Smart Solar Grass Cutter’s algorithm, scope, aims, applications and benefits. Grass Cutter industry heavily relies on manually operated grass cutters. However, in addition to using a significant amount of energy and contributing to air pollution, manually operated grass cutters also produce a significant amount of noise and vibration. Arduino based smart solar grass cutter is an intelligent automated grass cutter with ultrasonic sensors for obstacle detection.